From Organizational Welfare to Business Success: Higher Performance in Healthy Organizational Environments - Annamaria Di Fabio (Frontiers Research Topics, 2017)
This e-book provides insight into the link between employee health and productivity/performance, with a focus on how individuals, groups, or organizations can intervene in this relationship to improve both well-being and performance-related outcomes. Given the continuous changes that organizations and employees face, such as the aging workforce and continued economic turbulence, it is not surprising that studies are increasingly finding that employee health is related to job conditions. The papers in this e-book emphasize that organizations make a critical difference when it comes to employees' health and well-being. In turn, healthy employees help their organizations to flourish. Such findings are in line with the recent emphasis by both the International Labour Organization (ILO) and the United Nations (UN) on the importance of work for individual well-being and the importance of individual well-being for productive and sustainable economic growth (see e.g., ILO, 1985; World Health Organisation, 2007; UN, 2015). Overall, the papers report findings from a cumulative sample of nearly 19,000 workers and perspectives from 68 authors. They suggest that performance cannot be successfully achieved at the cost of health and well-being, and provide various perspectives and tools to guide future research and practice.